KOMPLEKSITAS PELANGGARAN PEMANFAATAN RUANG DITINJAU DARI TEORI KESADARAN HUKUM: KASUS TAMBANG DI PULAU OBI - Rumbiak, Joan Rossy; Bustani, Simona (Ensiklopedia Education Review, 2024)
Abstract: Every use of space needs to pay attention to the provisions in its Regional Spatial Plan and in order to realize orderly spatial planning, legal awareness is needed in the use of space. The main problem that is the main focus of this study is how the theory of legal awareness influences the Enforcement of Law on Violations of Spatial Utilization. This study uses a descriptive analysis research method, which means that this study is conducted to provide an overview of public awareness as part of the legal culture that influences a rule in force. The results of this study indicate that due to the many developments that are currently being carried out in our country, the mining sector has become a promising industry and public awareness in the use of space needs to be increased in order to create orderly spatial planning without new violations that arise more complex.Keywords: legal awareness, legal culture, spatial planning.